Problems in the Field of Emergency Risk Insurance in the Territory of the Republic of Uzbekistan (Eurasian Scientific Herald, 2022)
According to experts, the annual economic damage from the state of emergency restrains the socio-economic development ofboth the regions and the whole country. Currently, the negative processes taking place in the economy require a transition from gratuitous financing of expenses for the elimination of the consequences of emergency situations at the expense of the state budget to oblivion time-based planning and insurance of these expenses. The use of emergency insurance reduces the burden on all other sources of emergency response.